2016
DOI: 10.1016/j.ijplas.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic study of fundamental character and motion of dislocations in intermetallic Al2Cu

Abstract: Atomic scale study of the character and motion of dislocations in Al 2 Cu will provide insights into understanding the superior mechanical properties of Al-Al 2 Cu alloys. Using atomistic simulations, we studied seven potential slip systems (110)<001>, (010)<001>, (310)<001>, (010)<100>, (110)<1 0>, (110) < 1> and (112) < > in Al 2 Cu with body centered tetragonal structure. We found that three edge dislocations with Burgers vector <001> on glide planes (110), (010), and (310), show an extended core and are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 75 publications
5
9
0
Order By: Relevance
“…This situation was connected with the fact that for Al 2 Cu phase, the processes of recovery can proceed easier than for the α-Al phase. The obtained results are in accordance with the literature [ 24 , 25 ]. During deformation in Al 2 Cu phase, we observed a mechanism connected with non-conservative motion of glide dislocation.…”
Section: Resultssupporting
confidence: 92%
“…This situation was connected with the fact that for Al 2 Cu phase, the processes of recovery can proceed easier than for the α-Al phase. The obtained results are in accordance with the literature [ 24 , 25 ]. During deformation in Al 2 Cu phase, we observed a mechanism connected with non-conservative motion of glide dislocation.…”
Section: Resultssupporting
confidence: 92%
“…30 Using atomistic simulations with empirical potentials, we studied core structure of dislocations associated with these slip systems. 29 The potentials have been tested to well reproduce lattice constants, cohesive energy, elastic properties, as compared to first-principles density function theory calculations and experiments. 30,31 Additional calculation details specific to different separations are included in the Supplementary Information.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Using molecular dynamics (MD) simulations with empirical potentials, we studied core structure of <001> dislocation on (110) plane. 29 Disregistry analysis across the shear plane revealed that a [001] dislocation on (110) plane dissociates into two partials bonded by a planarextended core with a separation >1.5 nm (also see Figs. S1 and S2 in Supplementary Information).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, large particles remain in the grain boundaries due to the insufficient solution treatment temperature. It is well known that large particles in grain boundaries act as crack initiation sites, resulting in an increase in the brittleness [6,19,20]. On the other hand, the conventional solution treatment temperature of Al 2xxx alloys with 5.0 wt.% < Cu < 7.0 wt.% is high enough to induce the grain growth of Al grains.…”
Section: Introductionmentioning
confidence: 99%